Neutralization of the anticoagulant activity of low molecular weight heparin LU 47311 (Clivarin) in man by protamine chloride - Andrassy, Konrad; Eschenfelder, Volker; Weber, E. (Thrombosis research, 1994)
Bleeding induced by unfractionated heparin (UFH) can be antagonized by protamine as shown by normalization of thrombin time and aPTT. In order to learn about the neutralization capacity of protamine against the anticoagulant effects of LU 47311 a comparison study vs UFH was performed in 12 healthy male volunteers. Whereas the prolongation of aPTT and thrombin time induced by both heparins was reversed, inhibition of anti F Xa activity was not. A anti F Xa activity following injection of UFH was immediately antagonized by only 20 - 40 % with LU 47311. A rebound phenomenon of LU 47311 after protamine chloride was not detected. The platelet system remained unchanged.